The Effect of Cash Conversion Cycle, Sales Growth, and Financial Slack on Firm Value with Business Risk as a Moderating Variable - Maria Yovita R. Pandin; Marsha Via Anantasya; Erlyana Rizkya Zalfa (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to examine the effect of Cash Conversion Cycle, Sales Growth, and Financial Slack on Firm Value with Business Risk as a moderating variable in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Corporate value serves as a critical benchmark that demonstrates market participants' views on a company’s operational efficiency and long-term potential. An empirical quantitative method was adopted, leveraging archival data gathered from published annual disclosures and financial statements. Through a selective sampling framework, a total dataset of 60 firm-year observations was compiled for evaluation. ypothesis testing was executed utilizing Moderated Regression Analysis (MRA). The empirical evidence demonstrates that sales growth significantly boosts corporate worth. Conversely, neither the duration of the cash conversion cycle nor the volume of financial slack exerts any meaningful impact on corporate valuation. Additionally, empirical results indicate that business risk fails to function as a moderating force across all tested relationships. These outcomes imply that when evaluating corporate worth, market players tend to prioritize expansion in revenue streams over operational working capital agility or cash reserves.